2016
DOI: 10.1371/journal.pone.0158463
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex APLP System for High-Resolution Haplogrouping of Extremely Degraded East-Asian Mitochondrial DNAs

Abstract: Mitochondrial DNA (mtDNA) serves as a powerful tool for exploring matrilineal phylogeographic ancestry, as well as for analyzing highly degraded samples, because of its polymorphic nature and high copy numbers per cell. The recent advent of complete mitochondrial genome sequencing has led to improved techniques for phylogenetic analyses based on mtDNA, and many multiplex genotyping methods have been developed for the hierarchical analysis of phylogenetically important mutations. However, few high-resolution mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…This analysis was performed by using a multiplex system for analyzing mitochondrial single‐nucleotide polymorphisms (mtSNPs), which relies on a novel amplified product‐length polymorphism (APLP) method that uses inosine‐flapped primers and is specifically designed for the detailed haplogrouping of degraded mtDNA (Kakuda et al, 2016). This analysis was performed only for the samples for which the sequence analysis was successful.…”
Section: Methodsmentioning
confidence: 99%
“…This analysis was performed by using a multiplex system for analyzing mitochondrial single‐nucleotide polymorphisms (mtSNPs), which relies on a novel amplified product‐length polymorphism (APLP) method that uses inosine‐flapped primers and is specifically designed for the detailed haplogrouping of degraded mtDNA (Kakuda et al, 2016). This analysis was performed only for the samples for which the sequence analysis was successful.…”
Section: Methodsmentioning
confidence: 99%
“…The thermodynamics of the primers with inosine flaps has been proven to be less influenced by the sequence of PCR templates than the thermodynamics of the primers with 5′-flaps containing ordinary bases [33]. Furthermore, we reported that our inosine-flapped APLP method in the multiplex SNP analysis showed markedly higher sensitivity than that reported in various studies [61]. These features of 5′-flap primers are likely to have contributed to the high sensitivity observed in our sex determination method.…”
Section: Discussionmentioning
confidence: 93%
“…Thanks to the rapid development of sequencing technology, the genetics community has conducted a large number of assessments and analysis of mtDNA haplogroup diversity in the past few decades in different regions and ethnic groups in China. [18][19][20][21][22][23][24][25][26] MtDNA plays an important role in studying the matrilineal origins of various ethnic groups in the contemporary East Asian population. Although many problems remain to be solved and the related database is not perfect, the historical migration route of the population is still relatively clear.…”
Section: Discussionmentioning
confidence: 99%